Assessment of computed tomography findings and its association with Glasgow Coma Scale in patients with acute traumatic brain injury - Bagale, Deepak; Baral, Santosh; Pangeni, Roshan; Mallik, Mukesh (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Head injury is a serious public health concern, and 90% of deaths due to injury occur in low-income countries. Glasgow Coma Scale is the tool that is used to assess any head injury presented in the emergency department and baseline foundation to refer patient for computed tomography. This study aimed to assess the Computed Tomography scan findings in head injury and its association with Glasgow Coma Scale score grade. Methods: A descriptive cross-sectional study was conducted among 128 patients. Severity was scored on the Glasgow Coma Scale (3 to 15) while assessing patients in the emergency then categorised into mild (13 - 15), moderate (9 to 12), and severe (3 to 8). After the computed tomography scan, the diagnosis was noted, and association was analysed using Fisher's exact test and t-test. Results: The median age of the patient was 38.5 years. Females constituted 32.81% cases while 67.19% of the cases were males. The majority of the injuries were due to fall injuries (47.66%) and road traffic accidents (35.94%). The Computed Tomography diagnosis suggested that 64.84% of patients had some form of abnormality. According to the grade based on Glasgow Coma Scale, 81.25% of the patients had mild injury, 10.94% had moderate injury, and 7.81% had severe injury. There was no association of Glasgow Coma Scale with the number of intracranial injuries. However, significant association was seen with the intracranial Computed Tomography findings. Conclusions: Glasgow Coma Scale had a significant association with the intracranial injuries.